Pengembangan E-Modul Berbasis Team Games Tournament (TGT) Terhadap Kemampuan Berpikir Kritis pada Materi Sistem Pencernaan Manusia Kelas XI - Ardilla Sari; Syarifah Widya Ulfa (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to develop a Team Games Tournament (TGT)-based e-module on the human digestive system for 11th-grade high school students to enhance their critical thinking skills. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The participants were 11th-grade students at SMA Negeri 16 Medan. Data were collected using expert validation sheets, teacher and student response questionnaires, and pretest–posttest assessments. The results indicated that the e-module was classified as highly valid (92% by content experts and 91% by media experts). The practicality test showed very high practicality scores from both teachers (97.75%) and students (94%). Furthermore, the effectiveness test, measured by an N-gain of 0.80, demonstrated a significant improvement in students’ learning outcomes. In conclusion, the developed TGT-based e-module is valid, practical, and effective in enhancing students’ critical thinking skills in the study of the human digestive system. Keywords: ADDIE, Critical Thinking, E-module, Human Digestive System, Team Games Tournament